Neurolinguistics: subject, history, methods = Neurolingvistika: předmět, historie, metody - Mertins, Barbara; Flanderková, Eva (Slovo a slovesnost, 2012)
The present article deals with a number of issues relevant to neurolinguistics and, to a certain extent, also to psycholinguistics. First, it describes the development of neurolingustics from primarily clinically oriented studies in aphasiology to a new discipline focusing on language production and comprehension in healthy subjects, and locates neurolinguistics within contemporary cognitive science. In addition, it briefly addresses the relation and interplay between neuro- and psycholinguistics. Second, it introduces the main neuroimaging techniques (i.e. PET, fMRI, EEG, and MEG) used in current neurolinguistic studies and explains in approximate terms how these methods function and what linguistic research questions they can be used for. Finally, this article outlines several research questions central to neurolinguistic research and critically discusses several factors which complicate the interpretation of findings from this type of research.